2002
DOI: 10.1023/a:1023652920595
|View full text |Cite
|
Sign up to set email alerts
|

Investigation in central Italy of the possible association between Cryptococcus neoformans var. Gattii and Eucalyptus camaldulensis

Abstract: The authors present a worldwide review of isolations of Cryptococcus neoformans, var. neoformans and C. neoformans var. gattii from animals and vegetation, referring in particular to the already well-known association of the former variety with Eucalyptus camaldulensis. They then review the Italian situation relative to this association and their studies carried out in Central Italy: in Latina (Lazio), Pisa, Viareggio and Lake Massaciuccoli (Tuscany). From the 256 E. camaldulensis trees examined C. neoformans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…Eucalypts are in fact only one of Ͼ50 different species of tree that can provide an ecological niche for C. gattii (106)(107)(108)(109)(110). Environmental isolates have been obtained from Africa (33,(110)(111)(112), Asia (76,77,108), Australia (26,110,(113)(114)(115)(116)(117)(118), Europe (110,119,120), North America (38,110,121), and South America (122). In addition, it has been shown that plant material promotes fertility (108,(123)(124)(125) and may render C. gattii strains more pathogenic (125).…”
Section: Environmental Studiesmentioning
confidence: 99%
“…Eucalypts are in fact only one of Ͼ50 different species of tree that can provide an ecological niche for C. gattii (106)(107)(108)(109)(110). Environmental isolates have been obtained from Africa (33,(110)(111)(112), Asia (76,77,108), Australia (26,110,(113)(114)(115)(116)(117)(118), Europe (110,119,120), North America (38,110,121), and South America (122). In addition, it has been shown that plant material promotes fertility (108,(123)(124)(125) and may render C. gattii strains more pathogenic (125).…”
Section: Environmental Studiesmentioning
confidence: 99%
“…Veterinary isolates include strains recovered from cat, dog, magpie, and some isolates from striped grass mouse and degu living in a zoo [193–196]. Few C. neoformans strains were isolated from trees, namely, from Eucalyptus camaldulensis and oak tree [74, 197]. Most of the C. gattii natural isolates were from Eucalyptus camaldulensis , Douglas tree, carob tree, and stone pine [66, 74], whereas C. gattii animal infections were reported in a ferret and in some goats [65, 67].…”
Section: Combined Epidemiological Analysismentioning
confidence: 99%
“…It has been suggested that eucalyptus tree imports could be the route of introduction of C. gattii into the Pacific Northwest (20,21), particularly since one isolate (CBS7750) with a geno- (6,7,10,16,28,46,50,51). However, few of these studies have tested the hypotheses with genotypic data, and given the apparent global dispersal of C. gattii (31), it is difficult to demonstrate that C. gattii was absent from these areas prior to its isolation from imported trees.…”
Section: Vol 73 2007 Environmental Cryptococcus Gattii In British Cmentioning
confidence: 99%